PENGARUH KOMPENSASI DAN KOMPETENSI TERHADAP KEPUASAN KERJA APARATUR SIPIL NEGARA (ASN) PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN SIGI - Eva Warta I Pagisi; Agusman (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze the effect of compensation and competence on job satisfaction of the State Civil Apparatus (ASN) at the Staffing Agency and Human Resources Development of Sigi Regency. This research uses quantitative methods with saturated sampling techniques, where the entire population of 53 employees is sampled. The results showed that simultaneously compensation and competence had a significant effect on job satisfaction with a value of Fcount = 19,330 and a significance of 0.000 <0.05. Partially, compensation has a significant effect on job satisfaction with a regression coefficient of 0.627 and a significance value of 0.010 <0.05. Competence also has a significant effect on job satisfaction with a regression coefficient of 0.834 and a significance value of 0.000 <0.05. The determination test results show an R-Square value of 43.6%, which means that job satisfaction is influenced by compensation and competence by 43.6%, while the rest is influenced by other factors not examined.